2011
DOI: 10.1111/j.1365-2818.2011.03570.x
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing damage during FIB sample preparation of soft materials

Abstract: SummaryAlthough focused ion beam (FIB) microscopy has been used successfully for milling patterns and creating ultra-thin electron and soft X-ray transparent sections of polymers and other soft materials, little has been documented regarding FIB-induced damage of these materials beyond qualitative evaluations of microstructure. In this study, we sought to identify steps in the FIB preparation process that can cause changes in chemical composition and bonding in soft materials. The impact of various parameters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
143
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(150 citation statements)
references
References 44 publications
(51 reference statements)
4
143
0
Order By: Relevance
“…Their spectral patterns of aromatic/ olefinic carbon, aromatic ketone, and carboxyl carbon are typical of those observed from terrestrial coal (Cody et al 1998;Bassim et al 2012) and kerogen (Bernard et al 2012) and even extraterrestrial organic solids from chondritic meteorites and IDPs (e.g., Flynn et al 2003;Cody et al 2011). This does not necessarily imply that our category 3 particles are coal or chondritic organics, but the findings do suggest the presence of some form of heterogeneous macromolecule formed through chemical processing in a natural environment.…”
Section: Approach To Identify Category 3 Carbonaceous Particlesmentioning
confidence: 89%
See 1 more Smart Citation
“…Their spectral patterns of aromatic/ olefinic carbon, aromatic ketone, and carboxyl carbon are typical of those observed from terrestrial coal (Cody et al 1998;Bassim et al 2012) and kerogen (Bernard et al 2012) and even extraterrestrial organic solids from chondritic meteorites and IDPs (e.g., Flynn et al 2003;Cody et al 2011). This does not necessarily imply that our category 3 particles are coal or chondritic organics, but the findings do suggest the presence of some form of heterogeneous macromolecule formed through chemical processing in a natural environment.…”
Section: Approach To Identify Category 3 Carbonaceous Particlesmentioning
confidence: 89%
“…Similarly to TEM electron beam damage, ion beam damage from the FIB extraction of the samples is possible, although such damage is expected to be much smaller (Bassim et al 2012). Nevertheless, identical FIB conditions were applied for all the samples in this study, so it is unlikely that spectral differences between the samples could be attributed to the FIB procedure alone.…”
Section: Approach To Identify Category 3 Carbonaceous Particlesmentioning
confidence: 99%
“…The main challenge in preparing a TEM specimen of nanocomposite material is making a thin section of nanocomposite material without causing significant damage in the prepared specimen [13]. The following sections describe the general procedure for preparing a TEM specimen from a polymer nanocomposite material.…”
Section: Fib In Situ Lift Outmentioning
confidence: 99%
“…Mitigation strategies include the use of low beam currents, 79 changes in beam overlap during milling, 80 and use of mechanically supportive frames to maintain mechanical rigidity. 81 It was also shown that electron beam imaging during preparation of soft materials may chemically modify the structures.…”
Section: Ion-solid Interactionsmentioning
confidence: 99%